2006
DOI: 10.2466/pms.102.1.219-230
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Impairment in Patients with Parkinson's Disease on an Object-Based Negative Priming Task

Abstract: 12 nondemented patients with Parkinson's disease (M age = 67.3) and 12 normal control participants were administered an object-based attention task that enabled examination of both negative and positive priming. Unlike previous studies in which spatial-based attention tasks were used, results of the present study indicated that the patients displayed negative and positive priming not different from those shown by controls. These results suggest that certain object-based attentional processes may not be impaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 53 publications
2
20
0
Order By: Relevance
“…PD patients have previously been reported to have impaired space-based inhibitory processes (e.g., Filoteo et al, 1997;Hsieh, Lee, Hwang, & Tsai, 1997;Wright, Burns, Geffen, & Geffen, 1990), in the presence of intact object-based inhibition (e.g., Possin, Cagigas, Strayer, & Filoteo, 2006). Unlike previous studies that had separately examined space-and object-based inhibitory processes in different PD patients, Possin, Filoteo, Song, and Salmon (2009) examined both processes in the same patients.…”
Section: Ior Effects Are Influenced By Object Presencementioning
confidence: 73%
“…PD patients have previously been reported to have impaired space-based inhibitory processes (e.g., Filoteo et al, 1997;Hsieh, Lee, Hwang, & Tsai, 1997;Wright, Burns, Geffen, & Geffen, 1990), in the presence of intact object-based inhibition (e.g., Possin, Cagigas, Strayer, & Filoteo, 2006). Unlike previous studies that had separately examined space-and object-based inhibitory processes in different PD patients, Possin, Filoteo, Song, and Salmon (2009) examined both processes in the same patients.…”
Section: Ior Effects Are Influenced By Object Presencementioning
confidence: 73%
“…Since Parkinson's is caused by the degeneration of dopaminergic neurons, it is again of interest to note that chlorpromazine was associated with elevated NP effects in healthy participants (Beech et al, 1990). Both aforementioned studies applied spatial NP tasks; in an object-based paradigm, patients with Parkinson's did not differ from controls (Possin et al, 2006). Parkinson's disease is defined by motoric symptoms and deficits, so that the applied task properties (spatial vs. nonspatial) might be especially critical.…”
Section: Which Variables Can Explain Individual Differences In Np?mentioning
confidence: 99%
“…A number of studies using space-based attention tasks have identified altered inhibitory processes in PD (Filoteo et al, 1997; Filoteo et al, 2002; Gurvich, Georgiou-Karistianis, Fitzgerald, Millist, & White, 2007; Hsieh, Lee, Hwang, & Tsai, 1997; Wright, Burns, Geffen, & Geffen, 1990; Wylie & Stout, 2002), whereas other studies using object-based tasks show normal inhibition of attention in these patients (Lee, Wild, Hollnagel, & Grafman, 1999; Possin et al, 2006). This selective deficit in attention is similar to the selective deficits PD patients display on tests of spatial working memory as compared to tests of object working memory (Owen, Iddon, Hodges, Summers, & Robbins, 1997; Possin, Filoteo, Song, & Salmon, 2008; Postle, Jonides, Smith, Corkin, & Growdon, 1997).…”
mentioning
confidence: 99%
“…Although nondemented PD patients often perform similarly to neurologically healthy individuals on tests that require the facilitatory aspects of orienting (Bennett, Waterman, Scarpa, & Castiello, 1995; Goldman, Baty, Buckles, Sahrmann, & Morris, 1998), they frequently are impaired when conditions promote a conflict between task-relevant and irrelevant information, such as on tests of selective attention (Filoteo, Maddox, Ing, & Song, 2007), negative priming (Mari-Beffa, Hayes, Machado, & Hindle, 2005), and set shifting (Downes et al, 1989). It should be noted, however, that PD patients can perform normally on some attention tasks that require inhibition (Grande et al, 2006; Possin, Cagigas, Strayer, & Filoteo, 2006). …”
mentioning
confidence: 99%